Konsep Ramah Lingkungan dalam Perspektif Alquran, Hadis, dan Kitab Kuning di Pesantren - Rustam Ibrahim; A. Mufrod Teguh Mulyo; Lilis Fatimah (Jurnal Madania)
The Concept of environmentally-friendly in the Quran, Hadith, and Kitab Kuning in Pesantren. Environmental problems in Indonesia are worrying condition indicated by forest fires, landslide calamities, and floods in various parts of Indonesia. It informed that Indonesia is experiencing an environmental crisis. Pesantren as an Islamic educational institution has great potential in socializing environmentally-friendly concept in society. There are 27,218 pesantren[s] with 3,642,738 santri[s], located in rural areas, farms and mountains. This showed that pesantren has potential as a locomotive in environmental conservation. References of santri are Quran, hadith, and kitab kuning. The question is whether there is an environmentally-friendly concept in the Quran, hadith, and kitab kuning of pesantren, so it can be the guidance of santri in maintaining the environment. This research focuses on the concept, formulation, and urgency of environment in the perspective of Quran, hadith, and kitab kuning. The method used in this research is library research. Based on the research, there is a concept of environmentally-friendly in the Quran, hadith, and pesantren’s kitab kuning, that is, the obligation to maintain the environment. The formulation of environmentally-friendly concepts is a recommendation to maintain cleanliness, utilize empty land to be productive, greening spirits, create conservation areas, hard restrictions to pollute the environment, and severe sanctions for environmental destruction.